Modelling Outcomes of Collaboration in Building Information Modelling Through Gaming Theory Lenses - Olatunji, Oluwole; Sher, W.; Gu, N. (I3CON and BSRIA, 2010)
Construction project performance is vulnerable to process fragmentation and weak frameworks for sustaining objectivity and value integration between stakeholders, including clients, involved in the project development processes. For centuries, conventional construction processes have endured the challenges associated with this phenomenon. Several industry reports have suggested this situation is responsive to effective communication, collaboration, thorough integration and a passion for objectivity in data sharing and information management between key players. While entity-based computer-aided design (CAD) lacks the framework to facilitate an effective result in this direction, Building Information Modelling (BIM) has shown the potential for major improvements over the limitations of manual and CAD design methods. Three Game Theory models (Prisoner’s dilemma, Pareto Optima and Hawk-dove) have been proposed to mirror certain implications of players’ actions in BIM environment. In all the gaming lenses used, the study suggests that stakeholders and industry will only benefit when BIM is fully adopted. It has been established that when BIM is partially adopted, the compliant party is likely to benefit more, while the non-compliant party may not necessarily gain the same benefits. The study concluded that BIM means a lot to the industry; the industry cannot afford the consequences of failing to adopt BIM potentials and allied innovations in an era where digital technology is revolutionising other industries. Recommendations are made on areas for further research.